COMPARATIVE EFFECTIVENESS OF PHYSIOTHERAPEUTIC METHODS IN ATOPIC DERMATITIS IN CHILDREN - Achilova Donokhon Nutfullaevna; Nasimova Iroda Yakhyaevna (Web of Journals Publishing, 2025)
Atopic dermatitis (AD) is one of the most common chronic inflammatory skin diseases in children. In recent years, attention has increased to non-drug treatment methods, including physiotherapy. The aim of the study is to compare the effectiveness of various physiotherapeutic methods for AD in children. The paper analyzes the results of laser therapy, magnetic therapy and ultraviolet irradiation. The data obtained demonstrate that complex physiotherapeutic effects significantly improve the clinical course of AD, reduce the severity of itching and inflammation.
Keywords: Atopic dermatitis, children, physiotherapy, laser therapy, magnetic therapy, UFO.